Moxibustion Reduces Inflammatory Response in the Hippocampus of a Chronic Exercise-Induced Fatigue Rat - Li, Tian-ge; Shui, Ling; Ge, Dong-yu; Pu, Rong; Bai, Shu-mei; Lu, Jun; Chen, Ying-song (Frontiers in Integrative Neuroscience, 2019)
Accumulating data indicates that brain inflammation plays an important role in the pathophysiology of chronic exercise-induced fatigue. Moxibustion in traditional Chinese medicine has been found to alleviate exercise-induced fatigue. However, it remains unclear whether the effect of moxibustion is related to its anti-inflammatory properties. In this study, rats were exposed to 3-week exhaustive swimming to induce chronic exercise-induced fatigue. The body weight, exhaustive swimming time, tail suspension test and open-field test were observed. Real-time polymerase chain reaction (RT-PCR) was used to determine the mRNA expression of proinflammatory cytokines (interleukin-1β [IL-1β], interleukin-6 [IL-6], and tumor necrosis factor-α[TNF-α]), and enzyme-linked immunosorbent assay (ELISA) was used to detect IL-1β, IL-6, and TNF-α concentrations. Chronic exhaustive exercise significantly reduced the body weight and exhaustive swimming time, and increased tail suspension immobility time, which were reversed by moxibustion treatment. Compared with control rats, the mRNA and protein expression of IL-1β, IL-6, and TNF-α in the hippocampus was significantly increased in exhaustive swimming trained rats. Moxibustion significantly decreased the level of IL-6 in the hippocampus, but not affected IL-1β and TNF-α level significantly. Our results suggested that a potential inflammatory damage in the brain may be involved during chronic exhaustive exercise-induced fatigue. Moxibustion could attenuate the inflammatory impairment in exercise-induced fatigue, which might be mediated by inhibition of the proinflammatory cytokine IL-6 levels in the brain region.